Sentinel Node Detection in Head and Neck Malignancies: Innovations in Radioguided Surgery. (6th December 2009) - Vermeeren, L.; Klop, W. M. C.; van den Brekel, M. W. M.; Balm, A. J. M.; Nieweg, O. E.; Valdés Olmos, R. A.
Abstract : Sentinel node mapping is becoming a routine procedure for staging of various malignancies, because it can determine lymph node status more precisely. Due to anatomical problems, localizing sentinel nodes in the head and neck region on the basis of conventional images can be difficult. New diagnostic tools can provide better visualization of sentinel nodes. In an attempt to keep up with possible scientific progress, this article reviews new and innovative tools for sentinel node localization in this specific area. The overview comprises a short introduction of the sentinel node procedure as well as indications in the head and neck region. Then the results of SPECT/CT for sentinel node detection are described. Finally, a portable gamma camera to enable intraoperative real-time imaging with improved sentinel node detection is described.